2014
DOI: 10.1097/01.asw.0000443268.25288.63
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Candida albicans Following Exposure to 624-Nanometer Light from a Supraluminous Diode Array

Abstract: Appropriate doses of 624-nm light from a supraluminous diode array can inhibit the growth of C albicans in vitro. Three, 9, and 30 J/cm(2) are all effective dose levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Guffey et al reported that aBL at 405 nm was effective in inactivating Mycobacterium smegmatis , which is a non-pathogenic model system for the pathogenic Mycobacterium tuberculosis (Guffey et al, 2013a). All aBL exposures from 60 to 250 J/cm 2 produced a significant inactivation rate with the highest exposure (250 J/cm 2 ) demonstrating 100% inactivation.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…Guffey et al reported that aBL at 405 nm was effective in inactivating Mycobacterium smegmatis , which is a non-pathogenic model system for the pathogenic Mycobacterium tuberculosis (Guffey et al, 2013a). All aBL exposures from 60 to 250 J/cm 2 produced a significant inactivation rate with the highest exposure (250 J/cm 2 ) demonstrating 100% inactivation.…”
Section: Efficacy Of Antimicrobial Blue Light Inactivation Of Pathmentioning
confidence: 99%
“…In vitro inhibition of various bacteria using blue light (405–470 nm) has been frequently demonstrated (Guffey and Wilborn ,b; Guffey et al. ,b,c, ,b,c,d,e,f). To our knowledge, only (Guffey et al.…”
Section: Introductionmentioning
confidence: 99%
“…As Bush et al [4] have pointed out, finding alternative antimicrobial agents/ techniques must be a high-priority focus of current research. To this end, prior to this current experiment, we have been engaged in examining the bactericidal [5][6][7][8][9] and fungicidal [10] effects of visible and infrared light.…”
Section: Introductionmentioning
confidence: 99%
“…Dai, Gupta and Huang et al [2] recently demonstrated 405 nm light was effective in inhibiting P. aeruginosa in vivo related to mouse burn wounds. While higher doses (compared to those needed with S. aureus and P. aeruginosa) of light energy are required for effective inhibition of Mycobacterium smegmatis, blue light is an effective bactericidal agent against this organism [7,11,12]. Visible (primarily blue) light has also been shown to be an effective inhibitor of other microorganisms [13][14][15].…”
Section: Introductionmentioning
confidence: 99%